New Opportunities in Glycan Engineering for Therapeutic Proteins - Xiaotian Zhong; Aaron M. D’Antona; John J. Scarcelli; Jason C. Rouse (Antibodies, 2022)
Glycans as sugar polymers are important metabolic, structural, and physiological regulators for cellular and biological functions. They are often classified as critical quality attributes to antibodies and recombinant fusion proteins, given their impacts on the efficacy and safety of biologics drugs. Recent reports on the conjugates of N-acetyl-galactosamine and mannose-6-phosphate for lysosomal degradation, Fab glycans for antibody diversification, as well as sialylation therapeutic modulations and O-linked applications, have been fueling the continued interest in glycoengineering. The current advancements of the human glycome and the development of a comprehensive network in glycosylation pathways have presented new opportunities in designing next-generation therapeutic proteins.